Super-large particle size graded broken stone base layer and paving process thereof

By adopting the super-large particle size graded gravel base and its paving process, the problem of insufficient bearing capacity and deformation resistance of traditional graded gravel materials is solved, higher bearing capacity and durability are achieved, and construction and material costs are reduced.

CN119800791APending Publication Date: 2025-04-11GUANGXI ZHUANG AUTONOMOUS REGION BAISE HIGHWAY DEV CENT +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510239309.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditionally graded gravel materials have low bearing capacity and insufficient deformation resistance, making it difficult to adapt to major and medium-sized repair projects of national and provincial trunk roads with heavy load and above traffic levels.

Method used

The super-large particle size graded gravel base layer is used, and its components include 40-55 parts of 1# coarse particle gravel, 15-25 parts of 2# coarse particle gravel, 10-20 parts of 3# coarse particle gravel, 20-30 parts of fine particle gravel and 4-6 parts of water, and are formed by rolling through a specific paving process.

Benefits of technology

It significantly improves the overall bearing capacity and deformation resistance of the mixture, extends the durability and service life of the pavement structure, and reduces material costs and construction impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800791A_ABST
    Figure CN119800791A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of road construction, in particular to an oversized-particle-size graded broken stone base and a paving process thereof.The oversized-particle-size graded broken stone base is prepared from, by weight, 40-55 parts of 1 # coarse-particle-size broken stone, 15-25 parts of 2 # coarse-particle-size broken stone, 10-20 parts of 3 # coarse-particle-size broken stone, 20-30 parts of fine-particle-size stone powder and 4-6 parts of water; the larger the particle size of the gravels in the mixture is, the more the coarse particles are, the more the good skeleton interlocking structure is easily formed, the overall bearing capacity of the mixture is greatly improved, the super-large-particle-size graded gravel mixture forms the good mineral aggregate grading proportion, the coarse-particle-size gravels form the good skeleton interlocking structure, gaps in the middle are filled with the fine gravels, and the overall bearing capacity of the mixture is greatly improved. The optimal state that the coarse-particle-size gravel is stably embedded and extruded and the fine-particle-size stone powder is densely filled is formed, the overall deformation resistance of the mixture is improved, the construction uniformity of the mixture is improved, and compared with a traditional graded gravel base, the overall bearing capacity and the deformation resistance of a pavement structure can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road construction, and in particular to an ultra-large particle size graded crushed stone base and a paving process thereof. Background Art

[0002] The proportion of old cement pavement on secondary and lower highways has reached more than 60%. The cement pavement built earlier is gradually entering the end of its life, and large-scale cement pavements are facing major and medium repairs. At present, the maintenance of old cement pavements at the end of their life in China mainly adopts the structural scheme of gravelizing the old cement pavement and adding a transition layer (asphalt-stabilized gravel base, cement-stabilized gravel base, asphalt overlay of traditional graded gravel base) and asphalt overlay. A large number of engineering application practices have shown that: the asphalt-stabilized gravel base has the best effect, but the project cost is the highest; the cement-stabilized gravel base has many early reflective cracks and diseases, and the impact of not interrupting traffic construction is large;

[0003] The traditional graded crushed stone base has the lowest construction cost, but there are subsidence and cracking problems caused by insufficient bearing capacity in sections with heavy traffic. Therefore, there is an urgent need for transition layer materials with low cost, low impact and high bearing capacity.

[0004] Traditional graded crushed stone materials have relatively low bearing capacity and insufficient deformation resistance under heavy traffic conditions, making them difficult to adapt to major and medium-sized repair projects on national and provincial trunk roads with heavy traffic levels or above. Summary of the invention

[0005] The purpose of the present invention is to provide an ultra-large particle size graded crushed stone base and a paving process thereof, aiming to solve the problems of low bearing capacity and insufficient deformation resistance of uniformly graded crushed stone materials.

[0006] To achieve the above objectives, in the first aspect, the present invention provides an ultra-large particle size graded gravel base layer, the components of which include 40 to 55 parts of 1# coarse particle size gravel, 15 to 25 parts of 2# coarse particle size gravel, 10 to 20 parts of 3# coarse particle size gravel, 20 to 30 parts of fine particle size stone powder and 4 to 6 parts of water by weight.

[0007] Among them, the particle size range of the 1# coarse-grained gravel is 20mm~40mm, among which the pass rate of the 37.5mm sieve hole is 70%~95%, and the pass rate of the 19mm sieve hole is 0~10%; the particle size range of the 2# coarse-grained gravel is 10mm~30mm, among which the pass rate of the 31.5mm sieve hole is 90%~100%, and the pass rate of the 9.5mm sieve hole is 0~10%.

[0008] Among them, the particle size range of the 3# coarse-grained crushed stone is 5mm~10mm, among which the 9.5mm sieve hole pass rate is 90%~100%, and the 4.75mm sieve hole pass rate is 0~10%; the particle size range of fine-grained stone powder is 0~5mm, among which the 4.75mm sieve hole pass rate is 90%~100%, the 2.36mm sieve hole pass rate is 60%~90%, the 1.18mm sieve hole pass rate is 40%~75%, the 0.6mm sieve hole pass rate is 20%~55%, the 0.3mm sieve hole pass rate is 7%~40%, the 0.15mm sieve hole pass rate is 2%~20%, and the 0.075mm sieve hole pass rate is 0~20%.

[0009] In a second aspect, the present invention further provides a super-large particle size graded crushed stone base paving process, using the super-large particle size graded crushed stone base as described in the first aspect above, characterized in that it includes the following steps:

[0010] Weigh 40-55 parts of 1# coarse-grained crushed stone, 15-25 parts of 2# coarse-grained crushed stone, 10-20 parts of 3# coarse-grained crushed stone, 20-30 parts of fine-grained stone powder and 4-6 parts of water, and mix them evenly at a mixing station to obtain a mixture;

[0011] The mixture is evenly spread on the cement concrete pavement, and rolled using a steel wheel roller and a tire roller in turn to obtain a paved surface;

[0012] Sprinkling fine-grained stone powder and water on the paving surface in sequence, and rolling it again using the steel wheel roller, and opening it to traffic for 3 to 5 days after rolling to obtain a secondary paving surface;

[0013] Spraying the first layer of matrix asphalt on the secondary paving surface, spreading 2# coarse-grained crushed stone, then spraying the second layer of matrix asphalt, and finally spraying the second layer of matrix asphalt and spreading 3# coarse-grained crushed stone;

[0014] After the first layer of base asphalt and the second layer of base asphalt are cooled, the tire roller is used to compact them to obtain a super-large particle size graded crushed stone base layer.

[0015] The specific method of evenly laying the mixture on the cement concrete pavement and rolling it with a steel wheel roller and a tire roller in turn to obtain a paved surface is as follows:

[0016] The mixture is evenly laid on the cement concrete pavement, and the mixture is statically pressed back and forth by a steel wheel roller with zero amplitude;

[0017] The steel wheel roller then rolls the mixture back and forth with a vibration amplitude of 0.5 mm to 0.8 mm;

[0018] The steel wheel roller rolls the mixture back and forth with a vibration amplitude of 1 mm to 1.2 mm;

[0019] The tire roller rolls the mixture back and forth to obtain a paving surface.

[0020] The invention discloses an ultra-large particle size graded crushed stone base, which adopts ultra-large particle size 1# coarse particle size crushed stone, the particle size range of which reaches 20mm-40mm, and the passing rate of 37.5mm sieve hole is 70%-95%. The larger the particle size of the crushed stone in the mixture and the more coarse particles there are, the easier it is to form a good skeleton interlocking structure, thereby greatly improving the overall bearing capacity of the mixture. In the super-large particle size graded crushed stone mixture, 1# coarse particle size crushed stone: 2# coarse particle size crushed stone: 3# coarse particle size crushed stone: fine particle size stone powder: water = 40-55 parts: 15-25 parts: 10-20 parts: 20-30 parts: 4-6 parts, a good mineral grading ratio can be formed, so that the coarse particle size crushed stone forms a good skeleton interlocking structure, and the finer crushed stone fills the gaps in the middle, thus forming the best state of stable interlocking of coarse particle size crushed stone and dense filling of fine particle size stone powder, which not only improves the overall deformation resistance of the mixture, but also improves the uniformity of the mixture construction. Compared with the traditional graded crushed stone base, it can greatly improve the overall deformation resistance of the mixture. Improve the overall bearing capacity and deformation resistance of the pavement structure, improve the durability and service life of the pavement structure. Compared with the cement-stabilized crushed stone base, the super-large particle size graded crushed stone base can effectively save cement resources and reduce material costs by more than 15%. In addition, as an old cement pavement, the super-large particle size graded crushed stone base can homogenize the strength of the underlying layer, reduce the stress concentration phenomenon of the base structure, provide stable, reliable and uniform support for the surface layer, and significantly reduce the cracking of the pavement structure. The super-large particle size graded crushed stone base is less affected by traffic loads and does not require special curing. It can realize non-closed traffic construction, save at least 7 days of construction period, and reduce the long-term traffic congestion and low road transportation efficiency caused by road construction. The super-large particle size graded crushed stone base does not need to add cementitious materials, and there is no need to consider the adhesion performance between stone and cementitious materials. It has good applicability for sandstone, diorite, granite and other stones, greatly reducing the dependence on and over-exploitation of high-quality stone resources such as limestone, which is conducive to promoting local materials and promoting local economic development, and also further reducing the cost of engineering materials. The super-large-size graded crushed stone mixture is an improvement and innovation based on the traditional graded crushed stone. The nominal maximum particle size reaches 53mm and the mass of coarse particles above 19mm reaches more than 40%. It has a good skeleton embedded structure, which greatly improves the bearing capacity and deformation resistance of the road surface. In addition, the super-large-size graded crushed stone mixture is a bulk material with good anti-reflective cracking effect, small impact on non-interrupted traffic construction, and no maintenance is required after construction. Based on the economic applicability of this technology, it has broad application prospects in the maintenance projects of national and provincial trunk roads, and has significant social and economic benefits. It solves the problem of low bearing capacity and insufficient deformation resistance of the unified graded crushed stone material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 The present invention provides a flow chart of a super-large particle size graded crushed stone base paving process.

[0023] Figure 2 The invention is a flowchart of a specific method of evenly paving the mixture on a cement concrete pavement and rolling it with a steel wheel roller and a tire roller in turn to obtain a paved surface. DETAILED DESCRIPTION

[0024] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0025] In the first aspect, the present invention provides an ultra-large particle size graded crushed stone base layer, the components of which include, by weight, 40 to 55 parts of 1# coarse particle size crushed stone, 15 to 25 parts of 2# coarse particle size crushed stone, 10 to 20 parts of 3# coarse particle size crushed stone, 20 to 30 parts of fine particle size stone powder and 4 to 6 parts of water.

[0026] In the embodiment of the present invention, the particle size range of the 1# coarse-grained crushed stone is 20mm-40mm, of which the passing rate of the 37.5mm sieve hole is 70%-95%, and the passing rate of the 19mm sieve hole is 0-10%. The particle size range of the 2# coarse-grained crushed stone is 10mm-30mm, of which the passing rate of the 31.5mm sieve hole is 90%-100%, and the passing rate of the 9.5mm sieve hole is 0-10%; the particle size range of the 3# coarse-grained crushed stone is 5mm-10mm, of which the passing rate of the 9.5mm sieve hole is 90%-100%, and the passing rate of the 9.5mm sieve hole is 0-10%. 100%, the pass rate of 4.75mm sieve hole is 0-10%, the particle size range of fine particle size stone powder is 0-5mm, among which the pass rate of 4.75mm sieve hole is 90%-100%, the pass rate of 2.36mm sieve hole is 60%-90%, the pass rate of 1.18mm sieve hole is 40%-75%, the pass rate of 0.6mm sieve hole is 20%-55%, the pass rate of 0.3mm sieve hole is 7%-40%, the pass rate of 0.15mm sieve hole is 2%-20%, and the pass rate of 0.075mm sieve hole is 0-20%.

[0027] Screen size 9.5 4.75 2.36 1.18 0.6 0.3 0.15 0.075 Pass Rate 100 90~100 60~90 40~75 20~55 7~40 2~20 0~20

[0028] The volume ratio of the coarse aggregate of the super-large particle size graded crushed stone mixture after compaction is not less than 39%, and the CBR (bearing ratio) value is not less than 250. The gradation of the mineral material meets the following requirements:

[0029] Screen size 53 37.5 19 9.5 4.75 2.36 0.6 0.075 Pass rate (%) 90~100 70~90 40~60 25~40 20~35 15~25 5~10 0~5

[0030] See also Figure 1 to Figure 2 In a second aspect, the present invention further provides a super-large particle size graded crushed stone base paving process, using the super-large particle size graded crushed stone base as described in the first aspect above, characterized in that it includes the following steps:

[0031] S1 weigh 40-55 parts of 1# coarse-grained crushed stone, 15-25 parts of 2# coarse-grained crushed stone, 10-20 parts of 3# coarse-grained crushed stone, 20-30 parts of fine-grained stone powder and 4-6 parts of water, and mix them evenly in a mixing station to obtain a mixture;

[0032] S2: evenly paving the mixture on the cement concrete pavement, and rolling it using a steel wheel roller and a tire roller in turn to obtain a paved surface;

[0033] In the embodiment of the present invention, the mixed super-large particle size graded crushed stone mixture is evenly spread on the crushed cement concrete pavement, and the spreading thickness is 180 mm to 280 mm.

[0034] Specific method:

[0035] S21: evenly paving the mixture on the cement concrete pavement, and using a steel wheel roller to statically press the mixture back and forth with zero amplitude;

[0036] In the embodiment of the present invention, a steel wheel roller of not less than 20 tons is used to statically press the mixture back and forth for 1 to 2 times with zero amplitude.

[0037] S22: the steel wheel roller rolls the mixture back and forth with an amplitude of 0.5 mm to 0.8 mm;

[0038] In the embodiment of the present invention, a steel wheel roller of not less than 20 tons is used to vibrate and roll the mixture back and forth for 1 to 2 times with an amplitude of 0.5 mm to 0.8 mm.

[0039] S23 the steel wheel roller rolls the mixture back and forth with a vibration amplitude of 1 mm to 1.2 mm;

[0040] In the embodiment of the present invention, a steel wheel roller of not less than 20 tons is used to vibrate and roll the mixture back and forth 2 to 3 times with an amplitude of 1 mm to 1.2 mm.

[0041] S24: the tire roller rolls the mixture back and forth to obtain a paving surface.

[0042] In the embodiment of the present invention, a tire roller of not less than 25 tons is used to roll the mixture back and forth 3 to 4 times.

[0043] S3: spreading fine-grained stone powder and water on the paving surface in sequence, and rolling it again using the steel wheel roller, and opening it to traffic for 3 to 5 days after rolling to obtain a secondary paving surface;

[0044] In an embodiment of the present invention, fine-grained stone powder is evenly spread on the paving surface with a spreading thickness of 3mm to 5mm. Water is evenly spread on the surface of the fine-grained stone powder to keep the surface of the fine-grained stone powder moist. A steel wheel roller of not less than 20t is used to statically press the paving surface back and forth 1 to 2 times with 0 amplitude. After the rolling is completed, the traffic is opened for 3 to 5 days to slightly expose the coarse-grained gravel on the surface to obtain a secondary paving surface.

[0045] S4 spraying the first layer of matrix asphalt on the secondary paving surface, spreading 2# coarse-grained crushed stone, then spraying the second layer of matrix asphalt, and finally spraying the second layer of matrix asphalt and spreading 3# coarse-grained crushed stone;

[0046] In the embodiment of the present invention, the first layer of base asphalt is sprayed, the asphalt temperature is 160℃~170℃, and the spraying amount is 1.3kg / m 2 ~1.5kg / m 2 , then spread 2# coarse-grained gravel, every 1000m 2 The spreading amount is 12m 3 ~14m 3 ; Then spray the second layer of base asphalt, the asphalt temperature is 160℃~170℃, and the spraying amount is 0.9kg / m 2 ~1.1kg / m 2 Then spread 3# coarse-grained gravel. The spreading amount per 1000m2 should be controlled at 16m 3 ~18m 3 .

[0047] S5 After the first layer of base asphalt and the second layer of base asphalt are cooled, the tire roller is used to compact them to obtain a super-large particle size graded crushed stone base.

[0048] In the embodiment of the present invention, when the asphalt temperature drops below 50° C., a tire roller is used to roll the asphalt 2 to 3 times to obtain a super-large particle size graded crushed stone base structure.

[0049] This paving process can gradually compact the super-large particle size graded gravel base from a loose state, making the compaction process gradual, avoiding the crushing of coarse-grained gravel due to excessive compaction work, or the problem of difficulty in compaction due to insufficient compaction work, thereby ensuring the construction uniformity and compaction quality of the super-large particle size graded gravel base.

[0050] The dosage of each component in the comparative examples and embodiments is expressed in parts by weight:

[0051] type 20mm~40mm 10mm~30mm 5mm~10mm 0~5mm water Comparative Example 1 0 50 20 30 5 Comparative Example 2 10 42 18 30 5 Example 1 40 20 15 25 5 Example 2 45 18 12 25 5 Example 3 50 16 12 22 5 Example 4 55 15 10 20 5

[0052] The comparative examples and the examples were formed into test pieces according to the vibration compaction test method of T 0842 in the "Testing Procedures for Inorganic Binder Stabilized Materials for Highway Engineering" JTG 3441-2024, and the volume ratio of coarse aggregates above 19 mm and the CBR value in the mixed material test pieces of each example were tested respectively. The technical indicators are shown in the following table.

[0053]

[0054] As shown in the table above, in Comparative Example 1, since the nominal maximum particle size of the coarse-grained crushed stone is 31.5, and 1# coarse-grained crushed stone is lacking, the volume rate of coarse aggregates above 19 mm after compaction is low, and it is difficult for the mixture to form a good skeleton interlocking structure, so the CBR value of the mixture is relatively low. Although the nominal maximum particle size of the coarse-grained crushed stone in Comparative Example 2 can reach 53 mm, due to the relatively low content of 1# coarse-grained crushed stone, the volume rate of coarse aggregates above 19 mm after compaction is still low, and the skeleton interlocking structure of the mineral material in the mixture is weak. Therefore, although the CBR value has increased, the bearing capacity is still not high. In Examples 1 to 4, the content of 1# coarse-grained crushed stone reaches 40% to 55%, the nominal maximum particle size can reach 53 mm, and the volume rate of coarse aggregates above 19 mm after compaction reaches more than 39%. Therefore, the mineral material in the mixture can form a good skeleton interlocking structure, and the CBR value reaches more than 300. It can also be seen from the CBR values ​​of Examples 1 to 3 that the larger the volume ratio of coarse aggregates above 19 mm, the stronger the skeleton interlocking effect is, and the higher the bearing capacity is. However, considering that in actual engineering construction, the nominal maximum particle size of the mineral material is too large and the content of coarse-grained crushed stone is too high, segregation is more likely to occur during the paving process of the mixture, resulting in uneven bearing capacity of the pavement structure, thereby affecting the overall durability of the pavement structure. Therefore, the construction of the super-large particle size graded crushed stone base should strictly control the nominal maximum particle size of the mineral material and the content of coarse-grained crushed stone, and have good mechanical properties and use effects within the range described in the present invention.

[0055] Differences from traditional cement stabilized gravel base and the beneficial technical effects it brings:

[0056] Difference in mineral aggregate gradation: The nominal maximum particle size of the super-large particle size graded crushed stone mixture reaches 53mm, and the content of coarse aggregates above 19mm exceeds 40%; while the nominal maximum particle size of the traditional cement-stabilized crushed stone base is 31.5mm, and the content of coarse aggregates above 19mm does not exceed 25%. The content of coarse-grained crushed stone above 19mm in the mixture is higher, the nominal maximum particle size is larger, and it is easier to form a good skeleton interlocking structure, which is conducive to improving the overall strength and bearing capacity of the mixture.

[0057] Difference in material composition: Super-large particle size graded crushed stone mixture does not require the addition of cement binder, and the cement content of traditional cement-stabilized crushed stone base is usually 4% to 6%. Super-large particle size graded crushed stone mixture does not require the addition of cement, which can save more than 15% of material costs; because it does not contain cement binder, the mixture as a whole will not appear on the site of hardening, so there will be no shrinkage and shrinkage cracking, which solves the early cracking disease common in traditional cement-stabilized crushed stone base; in addition, super-large particle size graded crushed stone mixture does not add binder, and there is no need to consider the adhesion performance between stone and binder. It has good applicability for sandstone, diorite, granite and other stones, which greatly reduces the dependence on and over-exploitation of high-quality stone resources such as limestone, which is conducive to promoting local materials and further reducing the cost of raw materials.

[0058] Differences in paving technology: ① Different construction environment requirements: The traditional cement-stabilized gravel base has strict requirements on construction weather conditions, generally 10℃~30℃, to avoid thermal shrinkage or shrinkage cracking, while the super-large particle size graded gravel base has no strict requirements on construction weather, and the moisture content needs to be dynamically adjusted according to weather conditions, which significantly improves the construction period of the super-large particle size graded gravel base, and there is no need to consider the cracking problem during construction, which is more conducive to construction quality control; ② Different maintenance processes: After the construction of the traditional cement-stabilized gravel base is completed, it is necessary to close the traffic for maintenance for no less than 7 days, while the super-large particle size graded gravel base can be opened to traffic after the construction is completed, which can adapt to the uninterrupted traffic construction of the road network, greatly improving the convenience of road network maintenance and construction; ③ Different materials and processes for waterproof bonding layer: After 7 days of maintenance, the traditional cement-stabilized gravel base is usually sprayed with penetrating oil and adhesive oil to play the role of waterproof bonding layer. After the construction is completed, the traffic needs to be closed to prevent traffic vehicles from damaging the waterproof bonding layer and affecting the overall construction quality. After the super-large particle size graded gravel base is rolled, the two-oil and two-material waterproof bonding layer is paved, which is beneficial to improve the bonding effect between the base and the surface layer, and prevent rainwater from penetrating into the base to avoid water damage. The two-oil and two-material protective layer can be opened to traffic when it drops to room temperature, which greatly reduces traffic congestion and traffic accidents caused by closed traffic during road network construction, and has wide applicability in road network maintenance projects.

[0059] The above disclosure is only a preferred embodiment of an ultra-large particle size graded crushed stone base and its paving process of the present invention. Of course, this cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiments and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A super-large particle size graded crushed stone base, characterized in that ; The components include 40-55 parts of 1# coarse-grained crushed stone, 15-25 parts of 2# coarse-grained crushed stone, 10-20 parts of 3# coarse-grained crushed stone, 20-30 parts of fine-grained stone powder and 4-6 parts of water by weight.

2. The super-large particle size graded crushed stone base according to claim 1, characterized in that ; The particle size range of the 1# coarse-grained gravel is 20mm-40mm, among which the pass rate of the 37.5mm sieve hole is 70%-95%, and the pass rate of the 19mm sieve hole is 0-10%. The particle size range of the 2# coarse-grained gravel is 10mm-30mm, among which the pass rate of the 31.5mm sieve hole is 90%-100%, and the pass rate of the 9.5mm sieve hole is 0-10%.

3. The super-large particle size graded crushed stone base according to claim 1, characterized in that ; The particle size range of the 3# coarse-grained crushed stone is 5mm-10mm, among which the pass rate of 9.5mm sieve hole is 90%-100%, and the pass rate of 4.75mm sieve hole is 0-10%. The particle size range of fine-grained stone powder is 0-5mm, among which the pass rate of 4.75mm sieve hole is 90%-100%, the pass rate of 2.36mm sieve hole is 60%-90%, the pass rate of 1.18mm sieve hole is 40%-75%, the pass rate of 0.6mm sieve hole is 20%-55%, the pass rate of 0.3mm sieve hole is 7%-40%, the pass rate of 0.15mm sieve hole is 2%-20%, and the pass rate of 0.075mm sieve hole is 0-20%.

4. A super-large particle size graded crushed stone base paving process, using the super-large particle size graded crushed stone base as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: Weigh 40-55 parts of 1# coarse-grained crushed stone, 15-25 parts of 2# coarse-grained crushed stone, 10-20 parts of 3# coarse-grained crushed stone, 20-30 parts of fine-grained stone powder and 4-6 parts of water, and mix them evenly at a mixing station to obtain a mixture; The mixture is evenly spread on the cement concrete pavement, and rolled using a steel wheel roller and a tire roller in turn to obtain a paved surface; Sprinkling fine-grained stone powder and water on the paving surface in sequence, and rolling it again using the steel wheel roller, and opening it to traffic for 3 to 5 days after rolling to obtain a secondary paving surface; Spraying the first layer of matrix asphalt on the secondary paving surface, spreading 2# coarse-grained crushed stone, then spraying the second layer of matrix asphalt, and finally spraying the second layer of matrix asphalt and spreading 3# coarse-grained crushed stone; After the first layer of base asphalt and the second layer of base asphalt are cooled, the tire roller is used to compact them to obtain a super-large particle size graded crushed stone base layer.

5. A super-large particle size graded crushed stone base paving process, the super-large particle size graded crushed stone base as claimed in claim 4, characterized in that; The specific method of evenly paving the mixture on the cement concrete pavement and rolling it with a steel wheel roller and a tire roller in turn to obtain a paved surface is as follows: The mixture is evenly laid on the cement concrete pavement, and the mixture is statically pressed back and forth by a steel wheel roller with zero amplitude; The steel wheel roller then rolls the mixture back and forth with a vibration amplitude of 0.5 mm to 0.8 mm; The steel wheel roller rolls the mixture back and forth with a vibration amplitude of 1 mm to 1.2 mm; The tire roller rolls the mixture back and forth to obtain a paving surface.